Identifying latent profiles of psilocybin use - Gray, Bethany A., author; Rickard, Kathryn, advisor; Prince, Mark, advisor; Fidler, Deborah, committee member; Tompkins, Sara Anne, committee member (Colorado State University. Libraries, 2023)
Psilocybin, the hallucinogenic substance found in some mushrooms, may have medicinal and therapeutic uses. As such, it is garnering pronounced interest from the scientific community and general public. It is likely that psilocybin is on a trajectory to become more acceptable and sought out by researchers and individuals interested in its potential benefits. Traditionally, psilocybin has been used in does large enough to produce hallucinogenic effects; however, there are some reports of beneficial outcomes of psilocybin use with particularly small (i.e., micro) doses. It is likely that there are different patterns of psilocybin use, including using psilocybin in different dosages, frequencies, and for differing purposes, which have yet to be described in the literature. Thus, I sought to determine whether or not there are identifiable psilocybin use patterns of psilocybin use, to describe their defining characteristics, and test for differences on other important constructs, e.g., benefits, consequences, and reasons for use. This research uses mixture modeling to identify latent profiles of psilocybin use in a large population of adults endorsing lifetime psilocybin. Data for this project was sourced anonymously from subreddit community sites. I found three profiles indicated by frequency and quantity of psilocybin use. Auxiliary testing was used to evaluate differences among the profiles. The Chipper Profile (n =118) was associated with approximately 1-4 annual uses and between 0.75g and 1.0g dosages of dehydrated, psilocybin containing mushrooms. The Tripper Profile (n =428) was associated with a slightly higher psilocybin use frequency as the Chipper Profile (2 and 6 times annually), and self-reported dosages between 2 and 4g. The Microdose Profile (n =118), was related to substantively higher psilocybin use frequencies than the other two profiles (between 2 - 4 times a week) and a lower range of preferred dosages (between 0.25g - 0.75g). The profiles differed in the total number reasons participants reported having for their psilocybin use and the total number of benefits they reported experiencing. This can potentially be understood in relation to psilocybin use expectancies and motives to use. Additionally, every profile was associated with a low number of psilocybin use consequences, but the profiles did not significantly differ on this measure. Psilocybin seems to be distinct from other substances in that use frequency and quantity do not appear to impact one's risk of experiencing undesirable consequences of use. Further research is required to identify risk and protective factors for negative outcomes, as well as those that optimize the one's likelihood of experiencing psilocybin use benefits.